MEMITIGASI KONFLIK KEAGENAN DALAM PERSPEKTIF AL QUR’AN - Syarifuddin Syarifuddin Syarifuddin (AkMen JURNAL ILMIAH, 2019)
This agency conflict phenomenon raises the need to mitigate it. This motivates researchers to put forward the idea of ​​mitigating it based on the perspective of the Qur'an. There are several researchers who have proposed several concepts to mitigate this. But it always seems that the concept is not able to offer a comprehensive solution. The analytical method used is qualitative research. Data analysis is done by gathering concepts in the Qur'an. The concept is systematically made so that it can be used to mitigate agency conflicts. According to the perspective of the Qur'an, any cooperative relationship (agency) that is not cash must be based on the contract. The contract must be based on moral and ethical values ​​that must be held by both parties. The contract must also fulfill several terms and principles of the contract. The contract must also be accompanied by a witness who is a monitoring mechanism to the commitment of both parties in carrying out the contract. This research is expected to contribute in overcoming agency conflict. This model incorporates altruistic values ​​in modern management models. This model is expected to be able to mitigate the emergence of deviant behavior from both parties (agent and principal).